Trait Emotional Intelligence and Employee Engagement in ‎Gulf Countries: A Bibliometric Perspective - Alshehhia , Khulood Mohammed; Awang, Siti Rahmah (International Journal of Accounting and Economics Studies, 2025)
Employee engagement is a crucial factor in organizational success, as it significantly impacts productivity, job satisfaction, and overall ‎performance. This bibliometric study examines the relationship between trait emotional intelligence (TEI) and employee engagement within the ‎Gulf countries from 2015 to 2025. Using data extracted from the Scopus database, which consists of 530 documents. The study maps re‎search trends, identifies influential authors and journals, and highlights key thematic clusters. Findings indicate a growing scholarly interest ‎in the impact of trait EI on workplace performance, with significant contributions from leadership and psychological empowerment research. ‎The analysis reveals that facets of trait EI, such as happiness, self-motivation, and emotion regulation, are strong predictors of employee ‎engagement. Moreover, well-being exhibits a positive relationship with engagement, whereas emotionality demonstrates a negative correla‎tion. Leadership emerges as a critical factor, as emotionally intelligent leaders enhance engagement through improved motivation and com‎munication. This study provides valuable insights for organizations in the Gulf countries to develop EI-based interventions for workforce ‎optimization. Future research should investigate sector-specific applications and the impact of digital transformation on trait Emotional Intelligence (EI) and employee engagement. While Scopus offers broad coverage, the reliance on a single database may omit relevant regional ‎insights. Future studies are encouraged to use additional databases such as Web of Science or Google Scholar for triangulation‎.